2022
DOI: 10.1108/jmtm-01-2022-0014
|View full text |Cite
|
Sign up to set email alerts
|

The contingent effect of supply chain strategies on the relationship between supply chain integration and operational performance in manufacturing context

Abstract: PurposeThe purpose of this paper is to investigate the contingent effect of supply chain strategies on supply chain integration (SCI)-performance relationship in manufacturing organizations.Design/methodology/approachThis research hypothesized the moderation effect of agile, responsive, risk-hedging and efficient strategies on the relationship between SCI and operational performance (OP). Survey data were collected from a sample of 112 Egyptian manufacturing firms and analyzed using moderated regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…There is no evidence that improved integration with suppliers enhances service performance. By contrast, El Mokadem and Khalaf (2023) evidenced that supplier integration improves operational performance in manufacturing firms. Conversely, our study on the hotel sector revealed that supplier integration does not lead to an improvement in service performance.…”
Section: Discussionmentioning
confidence: 90%
“…There is no evidence that improved integration with suppliers enhances service performance. By contrast, El Mokadem and Khalaf (2023) evidenced that supplier integration improves operational performance in manufacturing firms. Conversely, our study on the hotel sector revealed that supplier integration does not lead to an improvement in service performance.…”
Section: Discussionmentioning
confidence: 90%
“…Overcoming challenges associated with linking supply chain strategies with energy networks presents opportunities for synergy and optimization through energy-efficient supply chain design, demand-side management, and renewable energy integration and offsetting [36]. Supply chain network design is critical in optimizing energy consumption and reducing environmental impacts [38].…”
Section: Linkages Between Supply Chain Strategies and Energy Networkmentioning
confidence: 99%
“…Designing supply chain networks with energy efficiency in mind involves considerations such as facility location, transportation modes, packaging, and inventory management. Implementing strategies such as consolidation of shipments, route optimization, and green logistics practices can minimize energy consumption and greenhouse gas emissions [36]. Therefore, the collaboration between supply chain managers, logistics providers, and energy experts can drive the integration of energy-efficient practices into supply chain design [43].…”
Section: Linkages Between Supply Chain Strategies and Energy Networkmentioning
confidence: 99%
“…Likewise, integration gives firms within the supply chain the opportunity to involve their partners in strategic collaborative relationships. Thus, supply chain integration (SCI) has been considered a strategic capability for companies and a source of competitive advantages (El Mokadem et al. , 2023; Liao et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%